FRAUD FINANCIAL STATEMENTS IN PENTAGON'S FRAUD PERSPECTIVE (Study on the Mining Sector Listed on the Indonesia Stock Exchange 2016 – 2020 Period) - Melda Tri Pratiwi; Dedik Nur Triyanto (JAF (Journal of Accounting and Finance), 2022)
Financial statement fraud is intentional or negligent by the company. Financial statement fraud is one type of fraud that often occurs in Indonesia. The occurrence of financial statement fraud in addition to causing internal conflicts within a company will also harm external parties in decision making. This study aims to detect financial statement fraud using a fraud pentagon analysis with pressure factors proxied by financial stability, external pressure and financial targets, opportunities proxied by ineffective monitoring and the nature of industry, rationalization proxied by auditor replacement, ability proxied by replacement directors, and arrogance proxied by the appearance of the CEO image in mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The population in this study is the mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period, which are 36 sample companies. The analytical technique used is logistic regression using SPSS 25 software. The results of this study indicate that simultaneously financial stability, external pressure, financial targets, ineffective monitoring, nature of industry, auditor replacement, replacement of directors, and the appearance of the CEO image have an effect on fraudulent financial reporting in mining sector companies listed on the Indonesia Stock Exchange for the period 2016 -2020. The partial test results show that the financial target and the nature of the industry have a positive effect, external pressure has a negative effect on fraudulent financial reporting. Financial stability, ineffective monitoring, replacement of auditors, replacement of directors, and the appearance of the CEO image have no partial effect on financial statement fraud. Based on the results in this study, the researcher provides theoretical and practical suggestions. Theoretically, researchers provide suggestions to academics and future researchers. Practically providing advice to companies as well as investors.